2009
DOI: 10.2353/ajpath.2009.090071
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Glucose Uptake Protects Liver from Lipopolysaccharide and d-Galactosamine, Acetaminophen, and Alpha-Amanitin in Mice

Abstract: Superiore di Sanità, Rome; and the Istituto Nazionale per lo Studio e la Cura dei Tumori, ‡ Milan, ItalyWe have recently observed that oral administration of D-glucose saves animals from lipopolysaccharide (LPS)-induced death. This effect is the likely consequence of glucose-induced activation of the sodiumdependent glucose transporter-1. In this study, we investigated possible hepatoprotective effects of glucose-induced, sodium-dependent, glucose transporter-1 activation. We show that oral administration of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Rumio et al 8 However, we observed no improvements in survival rate or pathologic damage (Figures 1a and c), even when glucose was injected 1 h before LPS/D-GalN administration, as described by Rumio et al 8 (Supplementary Figure 3). These inconsistent results may be attributed to the different survival periods of model mice.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Rumio et al 8 However, we observed no improvements in survival rate or pathologic damage (Figures 1a and c), even when glucose was injected 1 h before LPS/D-GalN administration, as described by Rumio et al 8 (Supplementary Figure 3). These inconsistent results may be attributed to the different survival periods of model mice.…”
supporting
confidence: 78%
“…31 In the present study, we observed short-term phosphorylation of ERK1/2 within 30 min after TNF-α stimulation, which peaked at 15 min, consistent with previous findings. 8 Although galactose enhanced phosphorylation of ERK1/2 slightly at 30 min, we speculate that this effect is abated. On the other hand, activity of NF-κB was significantly affected by galactose in hepatocytes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…LPS/D-Gal treatment is an established model of targeted LPS-dependent liver injury accompanied by a massive hepatic apoptosis and release of amino transferases ALT and AST [12,13]. As seen on figure 1, rat liver injury induced by injection of bacterial LPS only (Figure 1A) or LPS and D-Gal combination (Figure 1D) was accompanied by a fast rise of serum ASS levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with high overall mortality, ranging from 30 to 80%, depending on the underlying etiology. 1 The commonest causes are acute viral hepatitis, drug overdose, idiosyncratic drug reactions, and ingestion of other toxin. 2 Liver transplantation is the only therapy that has been proven beneficial, but the rapidity of progression and the variable course of ALF limit its application.…”
mentioning
confidence: 99%